Effects of fermented persimmon extract supplements on chemical composition and fermentation characteristics of barley silage. (26th December 2012) - Kim, Sang Bum; Kim, Dong Hyeon; Lee, Hyuk Jun; Amanullah, Sadar M.; Kim, Sam Churl
Abstract: This study was conducted to estimate the effect of fermented persimmon extract (FPE) supplementation levels on chemical composition and fermentation characteristics of barley silage. Barley forage was harvested at 25% dry matter and chopped to 5 cm lengths. The FPE was applied at 0, 0.4, 0.8 and 1.6 g/kg of barley forage (fresh weight basis). After sub‐sampling of barley forages (0 day), a total of 64 laboratory mini silos (5 kg capacity) were ensiled to generate quadruplicate data from each of four treatments for four ensiling durations (2, 6, 40 and 120 days). The chemical compositions and in vitro digestibility of barley forage (0 day) were not affected by FPE supplementation. However, the content (L, P = 0.035) and in vitro digestibility (L, P = 0.041) of neutral detergent fiber on 120‐day barley silage decreased by increasing FPE supplements. Acetate content of barley silage ensiled for 120 days increased (Q, P = 0.004) by increasing FPE supplements, whereas pH (L, P < 0.001), lactate content (Q, P < 0.001) and lactate‐to‐acetate ratio (Q, P < 0.001) decreased. These results indicate that addition of FPE can increase the acetate content which has potential to increase aerobic stability.